Recent research progress in tetrodotoxin detection and quantitative analysis methods - Lin, Chao; Li, Qirong; Liu, Dong; Feng, Qiang; Zhou, Hengzong; Shi, Bohe; Zhang, Xinxin; Hu, Yurui; Jiang, Xinmiao; Sun, Xiaoming; Wang, Dongxu (Frontiers in Chemistry, 2024)
Tetrodotoxin (TTX) is a highly potent and widely distributed ion-channel marine neurotoxin; it has no specific antidote and poses a great risk to human health. Therefore, detecting and quantifying TTX to effectively implement prevention strategies is important for food safety. The development of novel and highly sensitive, highly specific, rapid, and simple techniques for trace TTX detection has attracted widespread attention. This review summarizes the latest advances in the detection and quantitative analysis of TTX, covering detection methods based on biological and cellular sensors, immunoassays and immunosensors, aptamers, and liquid chromatography-mass spectrometry. It further discusses the advantages and applications of various detection technologies developed for TTX and focuses on the frontier areas and development directions of TTX detection, providing relevant information for further investigations.